Reflections about researching interethnic studies in multiethnic Kuala Lumpur - Rokis, Rohaiza; Muhammad Fauzi, Fatin Nadhirah; Tajuddin, Nor Azlin; Woon, You Huay (International Academic Research Journal of Social Sciences, 2020)
This article presents the challenges faced by researchers in conducting an interethnic study in Kuala Lumpur. The available various frameworks applied in interethnic studies across various contexts indicate that interethnic studies are not challenge-free. The data derived from the sociological research on B40 urban women across three major ethnic groups in Malaysia: Malay, Chinese, and Indian. Based on the analyses originated from the researchers’ reflection and observation notes, several challenges, inclusive of overcoming language barrier, employing different research approaches, and dealing with gatekeepers, emerged throughout the fieldwork. The research provided some challenges faced by researchers in performing an interethnic study in the context of B40 urban women in Kuala Lumpur. These challenges are presented to assist future researchers who are interested in interethnic studies. Despite the available limitations, the research provide additional information to enhance ethnic relations and promote cohesion between and among groups. In particular, the research seeks to enrich the knowledge of research methodology involving interethnic studies, a field that would impact in a culturally diverse land, such as Malaysia.